Summer savory (Satureja hortensis) can reduce spermatotoxic effects of Doxorubicin in rats - Ali Shalizar Jalali; Gholamreza Najafi; Parisa Rahimzadeh (Babol University of Medical Sciences, 2015)
Introduction: Application of doxorubicin (DOX), an anticancer anthracycline antibiotic, carries the risk of serious dose-dependent toxicity to non-target tissues. The aim of this study was to investigate whether DOX-induced spermatotoxicity could be prevented by using the Satureja hortensis hydroalcoholic extract (SE).   Methods: Male Wistar rats were randomly divided into four groups of six rats each. DOX was administered to two groups of rats in 5 equal intraperitoneal injections over a period of 4 weeks (accumulated dose of 20 mg/kg). One of these groups received SE at a dose of 100 mg/kg per day subcutaneously for 28 days along with DOX. A vehicle treated control group and a SE control group were also included. Results: Epididymal sperm analyses revealed that DOX caused significant decreases in sperm concentration, viability and motility along with elevated sperm abnormality, while SE co-administration provided marked normalization in the sperm quantity and quality compared to the DOX-only treated group.  Conclusion: It is reasonable to suppose that protective effects of SE against DOX-induced reproductive toxicity might have been related to the antioxidative and anti-inflammatory effects of this substance.